"You Can Be More": Farscape, Melodrama, and Space Opera Revisited. - Lavigne, Carlen (MOSF Journal of Science Fiction, 2019)
The science fiction television series Farscape (Syfy, 1999-2003) was notable f or its subversive blend of science fiction and soap opera conventions, which allowed the series to present as a complex study of gender and sexuality. However, small but overt elements serve to undermine the subtler feminist or queer potential of Farscape's overall structures. This article examines the series, specifically in light of later-season e pisodes and the two-part conclusion, T he Peacekeeper Wars, in examining whether Farscape successfully maintains its position as groundbreaking cult television.